The Relationship Of Nurse Caring Behavior With Anxiety Level In Covid 19 Patients In The Tulip And Orchid Isolation Room UPT RSUD Deli Serdang - Nurlela Petra saragih; Intan Mutia Rahmi; Rini Elvira Hutabarat; Sontina Saragih (Institute of Computer Science (IOCS), 2022)
Coronavirus 19 (COVID-19) has been declared a world pandemic by WHO (WHO, 2020). Anxiety in patients with a confirmed COVID-19 suspicion requires close medical observation and isolation during treatment. Nurses are one of the health professionals who still have to work and continue to serve in the current Covid-19 pandemic situation. Based on this, the researchers were interested in obtaining information about